Comprehensive Analysis of TIG Welded Inconel–718 Alloy for Different Heat Input Conditions - Jerold Jose, P; Dev Anand, M (International Journal of Engineering and Technology, 2018)
In this research, the effects of heat input on tensile properties and microstructure were investigated for super alloy Inconel-718 sheets weld by Tungsten Inert Gas (TIG) welding process. The tensile properties and microstructure of weld joints were evaluated. The experiment was conducted with six different combinations of welding parameters like welding current, voltage and welding speed, which were give in six different welding heat input combinations of welding parameters. The experimental results shows that the welding joints weld with low welding heat input was yield higher tensile properties. From the experimentation it was understand that the tensile properties increases when the welding heat input decrease. Drastic grain coarsening was evidenced when the heat input was increases. For the weld joints experimented in this research it was also observed that amount of laves phase was increased with increase in the welding heat input which is the major fact for noticeable variation in the ultimate tensile strength of the weld joints welded by TIG welding process with different welding heat input.Â